Preformulation Studies of Ezetimibe-Simvastatin Solid Dispersions in the Development of Fixed-Dose Combinations - Agata Górniak; Adrianna Złocińska; Mateusz Trojan; Adrianna Pęcak; Bożena Karolewicz (MDPI AG, 2022)
Two active pharmaceutical ingredients (APIs) with limited solubility, simvastatin and ezetimibe, prepared as a drug-drug solid dispersion (SD) was evaluated for physicochemical, microstructural, and aqueous dissolution properties. The simvastatin-ezetimibe SD was prepared using the co-grinding method in a wide range of weight fractions and differential scanning calorimetry (DSC) and X-ray powder diffraction (XRPD) were used to perform the phase composition analysis. DSC studies confirmed that simvastatin and ezetimibe form a simple eutectic phase equilibrium diagram. Analysis of Fourier transform infrared spectroscopy (FTIR) studies excluded strong interactions between the APIs. Our investigations have revealed that all studied dispersions are characterized by substantially improved ezetimibe dissolution regardless of simvastatin content, and are best when the composition oscillates near the eutectic point. Data obtained in our studies provide an opportunity for the development of well-formulated, ezetimibe-simvastatin fixed-dose combinations (for hypercholesterolemia treatment) with reduced ezetimibe dosages based on its dissolution improvement.